Extraction and Hydrophobic Modification of Cotton Stalk Bark Fiber - Ya-Yu Li; Guang-Ming Du; Xin-Jie Feng; Ya-Wei Mu; De-Qiang Li (International Journal of Polymer Science)
Cotton stalk bark fiber (CSBF) was extracted at high temperature and under high pressure, under the condition of the alkali content of 11 wt%. Experimental results proved that the extraction yield of CSBF was 27.3 wt%, and the residual alkali concentration was 2.1 wt%. Then five kinds of modifiers including methyl methacrylate (MMA), MMA plus initiator, epoxy propane, copper ethanolamine, and silane coupling agent were chosen to modify the surface of CSBF. It was found by measuring water retention value (WRV) that these five kinds of modifiers were all effective and the silane coupling agent was best modifier among all. The optimal modifying conditions of silane coupling agent were obtained: modifier concentration was 5%, the mixing temperature was 20°C, the mixing time was 1 h, and vacuum drying time was 1 h. Under the optimal condition, the WRV of the modified CSBF was 89%. It is expected that these modified CSBF may be a filler with strengthening effect in wood plastic composites (WPC) fields.